2019
DOI: 10.1021/acs.iecr.9b03064
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Pervaporative Desulfurization Performance of Pebax-Ag+@MOFs Hybrid Membranes by Integrating Multiple Transport Mechanisms

Abstract: Polymeric dense membranes for separating molecules with similar properties in liquid mixture according to solution-diffusion mechanisms are often constrained by trade-off effects. Integrating a facilitated transport mechanism and a sieving mechanism into membranes is a preferred approach to address this issue. Herein, amine-functionalized titanium-based metal–organic frameworks (NH2-MIL-125­(Ti)) immobilized with Ag+, Ag+@NH2-MIL-125­(Ti), was synthesized and hybrid membranes were fabricated for pervaporative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The comparison of the desulfurization of the as-prepared membrane in this study with recent studies ,,, is shown in Figure . It can be seen that the enrichment factor of the membrane in this study is higher than that of other membranes reported previously, whereas the permeation flux of the membrane is lowest.…”
Section: Resultsmentioning
confidence: 65%
“…The comparison of the desulfurization of the as-prepared membrane in this study with recent studies ,,, is shown in Figure . It can be seen that the enrichment factor of the membrane in this study is higher than that of other membranes reported previously, whereas the permeation flux of the membrane is lowest.…”
Section: Resultsmentioning
confidence: 65%
“…This study recommends the integration of multiple transport mechanisms by using MOFs as nanofillers to achieve superior separation performance. [60] The depletion of fossil fuels has sparked enormous interest to develop alternative energy resources such as renewable biofuels. Compared with conventional fuels, biofuels are environmentally benign and carbon neutral with less emission of gaseous pollutants.…”
Section: Liquid Fuel Purificationmentioning
confidence: 99%
“…HDS is a nonselective hydrogenation process that requires high temperature and high pressure. The process also requires substantial quantities of H2, which is expensive [6][7][8]. Therefore, new catalysts or deep desulfurization method is required.…”
Section: Introductionmentioning
confidence: 99%